2014
DOI: 10.1523/jneurosci.5167-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Acts via Lateral Hypothalamic Area Neurotensin Neurons to Inhibit Orexin Neurons by Multiple GABA-Independent Mechanisms

Abstract: The adipocyte-derived hormone leptin modulates neural systems appropriately for the status of body energy stores. Leptin inhibits lateral hypothalamic area (LHA) orexin (OX; also known as hypocretin)-producing neurons, which control feeding, activity, and energy expenditure, among other parameters. Our previous results suggest that GABAergic Nts neurons to mediate two distinct GABA-independent mechanisms of inhibition: the presynaptic inhibition of excitatory neurotransmission and the opening of K ATP channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 45 publications
(16 reference statements)
4
85
2
Order By: Relevance
“…Previous neuroanatomical studies have also implicated these sites in inflammatory anorexia (73)(74)(75)(76). It has also been suggested that melanocortin signaling in GABAergic interneurons contacting orexin neurons in the LHA might contribute to the regulation of appetite (40,77). Interestingly, we and others have previously demonstrated that LPS could reduce the activity of LHA neurons, including orexin neurons, in fasted animals (18,78).…”
Section: Central Viscerosensory Pathways Involved In Inflammatory Anomentioning
confidence: 61%
“…Previous neuroanatomical studies have also implicated these sites in inflammatory anorexia (73)(74)(75)(76). It has also been suggested that melanocortin signaling in GABAergic interneurons contacting orexin neurons in the LHA might contribute to the regulation of appetite (40,77). Interestingly, we and others have previously demonstrated that LPS could reduce the activity of LHA neurons, including orexin neurons, in fasted animals (18,78).…”
Section: Central Viscerosensory Pathways Involved In Inflammatory Anomentioning
confidence: 61%
“…For instance, LHA Nts neurons might co-release GABA onto VTA GABA interneurons, thereby disinhibiting DA neurons and promoting DA signaling (Nieh et al, 2016). LHA Nts neurons also project locally and inhibit neighboring hypocretin/orexin neurons (Goforth et al, 2014; Leinninger et al, 2011), which could decrease food intake, especially in a food-restricted state. Our data thus reveal that LHA Nts neurons are important mediators of central anorectic Nts action via NtsR1.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is a circulating anorexigenic and pro-inflammatory adipokine produced by the adipose tissue, which reduces both endocannabinoid (Di Marzo et al, 2001) and OX-A (Goforth et al, 2014) signaling in the hypothalamus. Its levels are altered in obesity as well as during anorexia and bingeeating disorder (Monteleone et al, 2000;Cristino et al, 2014, for review).…”
Section: Introductionmentioning
confidence: 99%